Tinjauan Yuridis Pertanggungjawaban Pidana Pelaku Pertambangan Tanpa Izin (Tambang Ilegal) dalam Perspektif Hukum Pidana Lingkungan - Sanjaya, Muhammad Wanda; Ritonga, Rifandi; Ainita, Okta (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
This study examines the criminal liability of perpetrators of illegal mining activities from the perspective of environmental criminal law in Indonesia, with a specific focus on the Decision of the Kalianda District Court Number 150/Pid.Sus/2025/PN Kla. Illegal mining remains a serious and persistent problem due to its significant negative impacts on environmental sustainability, state revenue, and social order. Unlicensed mining activities often lead to environmental degradation, pollution, and long-term ecological damage, which undermine the constitutional mandate of sustainable natural resource management. This research aims to analyze the fulfillment of criminal offense elements in illegal mining cases, the form of criminal liability imposed on offenders, and the effectiveness of environmental criminal law enforcement in practice. The study employs a normative juridical research method using statutory and case approaches. Legal materials consist of primary legal sources such as legislation and court decisions, as well as secondary and tertiary legal materials in the form of legal doctrines and scholarly works. All materials are analyzed qualitatively through legal interpretation and systematic analysis. The findings indicate that the defendants’ actions fulfilled all elements of illegal mining offenses as regulated under Law Number 3 of 2020 concerning Mineral and Coal Mining. Criminal liability was imposed in the form of imprisonment and fines, reflecting the role of criminal law as a repressive instrument for environmental protection. Nevertheless, law enforcement still encounters various obstacles, including weak supervision, limited institutional coordination, and low public legal awareness. Therefore, strengthening preventive measures and ensuring consistent law enforcement are essential to achieve sustainable environmental protection.